"Living as Monks" and Fools for Christ,s Sake in the Russian Baptist Brotherhood - Prokhorov, Constantine (Bogoslovskie razmyšlenija, 2010)
The author compares the Russian-Ukrainian Baptist brotherhood - first of all, in its late Soviet form - with the Russian Orthodox concept of "monasticism in the world." Characteristic examples of asceticism among Russian Baptists, in some cases bordering on foolishness for Christ's sake, are described and analyzed, which to some extent may be explained by what is common to Christians of Russia, namely the "Eastern Christian" understanding of holiness. In addition, the parallels between some known hagiographical narratives of Russian Baptists and the "Lives of the Saints" are drawn; both external and internal similarities are noted. The article attempts to clear up the misunderstandings connected with the subject and at the inter-confessional level, in the context of church history in general, to demonstrate the legitimacy of the thesis of the "monastic way" of Russian Baptists. The work is based to a large measure on primary sources - books, articles, and interviews, reflecting the tradition of the Evangelical-Baptist brotherhood before the beginning of perestroika.